2013
DOI: 10.1158/0008-5472.can-12-0759
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Antigen-Transfected, NKT Cell Ligand–Loaded, Human Cells Elicits Robust In Situ Immune Responses by Dendritic Cells

Abstract: Both innate and adaptive immunity are crucial for cancer immunosurveillance, but precise therapeutic equations to restore immunosurveillance in patients with cancer patients have yet to be developed. In murine models, a-galactosylceramide (a-GalCer)-loaded, tumor antigen-expressing syngeneic or allogeneic cells can act as cellular adjuvants, linking the innate and adaptive immune systems. In the current study, we established human artificial adjuvant vector cells (aAVC) consisting of human HEK293 embryonic kid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…For in vitro transcription, these plasmids were linearized by restriction enzyme digestion, purified by a QIAquick PCR Purification Kit (QIAGEN), and used as a template. The RNAs were generated under a T7 promoter sequence on the vectors using an mMESSAGE mMACHINE T7 Ultra Kit (Ambion), as previously described (22). To load NIH3T3 cells with a-GalCer, the cells were cultured for 48 h in the presence of 500 ng/ml a-GalCer and then washed three times before transfection.…”
Section: Preparation Of Cd1d-nih3t3/gal-ovamentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro transcription, these plasmids were linearized by restriction enzyme digestion, purified by a QIAquick PCR Purification Kit (QIAGEN), and used as a template. The RNAs were generated under a T7 promoter sequence on the vectors using an mMESSAGE mMACHINE T7 Ultra Kit (Ambion), as previously described (22). To load NIH3T3 cells with a-GalCer, the cells were cultured for 48 h in the presence of 500 ng/ml a-GalCer and then washed three times before transfection.…”
Section: Preparation Of Cd1d-nih3t3/gal-ovamentioning
confidence: 99%
“…To maximally harness such immunological cascades, we established an efficient system using cells bearing a cell-associated Ag along with the iNKT cell ligand, a-galactosylceramide (a-GalCer). For example, we used iNKT ligand-loaded, tumor-associated Ag (TAA)-expressing CD1d + tumor cells (tumor/Gal) (19)(20)(21) or allogeneic fibroblasts loaded with a-GalCer transfected with TAA mRNA (16,22).…”
mentioning
confidence: 99%
“…On the basis of these evidences, we previously illustrated the concept of a unique approach of using NKT ligand-loaded CD1d þ allogeneic cells transfected with tumor antigen mRNA as artificial adjuvant vector cells (aAVC; refs. 16,17). The first generation of aAVCs demonstrated certain of its immunologic features inducing both innate and adaptive immunity in the lymphoid organs through antigen-captured DCs in situ.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] We and other researchers previously demonstrated that dendritic cell (DC) therapy increases the activation of NK cells against tumor cells [22][23][24] and that CD1d C cells loaded with invariant NKT cell ligand generate NKT cell-mediated protection against tumor cells. 25 Although there are reports in tumor-bearing mice of interactions between NK cells and various types of myeloid cells, i.e., DCs, macrophages, MDSCs, it is unclear whether NK cells influence the number or function of MDSCs.…”
Section: Introductionmentioning
confidence: 99%